2007
DOI: 10.1089/dna.2007.0609
|View full text |Cite
|
Sign up to set email alerts
|

In VitroInvestigation of the Apoptotic Effect of Heparin on Lymphoblasts by Using Flow Cytometric DNA Analysis and Fluorometric Caspase-3 and -8 Activities

Abstract: The apoptotic effect of heparin on the lymphoblasts obtained from 12 newly diagnosed children with acute lymphoblastic leukemia (ALL) was investigated in vitro. The lymphoblasts were incubated with 0, 10, and 20 U/mL heparin concentrations at 0, 1, and 2 h. The percentages of the apoptotic lymphoblasts were calculated by flow cytometry (FCM), and activities of caspase-3 and -8 were simultaneously measured by fluorometric protease activity method. The apoptotic effect of heparin on the lymphoblasts was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 19 publications
3
10
0
Order By: Relevance
“…We demonstrated in this study that the greatest proliferation effect of heparin and the highest SPF ratio were determined in 20 U/ml concentration at 1 h. Recent studies from Erduran et al [30] determined that the greatest apoptotic effect of heparin on the lymphoblasts was detected in 20 U/ml concentration at 1 h. The results of some recent studies were found to be concordant [28][29][30]. Apoptosis and proliferation are important regulators of normal development and homeostasis in the bone marrow.…”
Section: Aksoy Et Al Heparin and Human B-lymphoblast Cell Cyclesupporting
confidence: 71%
“…We demonstrated in this study that the greatest proliferation effect of heparin and the highest SPF ratio were determined in 20 U/ml concentration at 1 h. Recent studies from Erduran et al [30] determined that the greatest apoptotic effect of heparin on the lymphoblasts was detected in 20 U/ml concentration at 1 h. The results of some recent studies were found to be concordant [28][29][30]. Apoptosis and proliferation are important regulators of normal development and homeostasis in the bone marrow.…”
Section: Aksoy Et Al Heparin and Human B-lymphoblast Cell Cyclesupporting
confidence: 71%
“…Multicycle analyse program was used to detect of apoptosis. The blast cells ongoing to apoptosis were dyed with PI less than the non-apoptotic cells and showed hypodiploid sub-G1 peak on the DNA histogram [4][5][6][7]12,13].…”
Section: Methodsmentioning
confidence: 99%
“…Beside its anticoagulant, anti-inflammatory, antihypertensive and antiproliferative effects [1][2][3], heparin has the apoptotic effect in lymphoblasts, in vitro [4][5][6]. Manaster et al [7] claimed that 50, 100 and 200 U/ml concentrations of heparin induce apoptosis in human peripheral blood neutrophils, in vitro.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations